Taxes and payments paid by individuals, the impact on their financial situation - N. Z. Zotikov (Вестник университета)
In accordance with the current tax legislation, on an equal footing with organisations and individual entrepreneurs, individuals who do not have income from business pay taxes on income from labor activities in organisations and taxes on property they own: transport, land, and personal property tax, as well as other non-tax payments (housing and communal services, etc.). The article analyses the role and importance of taxes paid by individuals in the budgets of various levels, non-tax mandatory payments, their impact on the financial situation of individuals. The relevance of the study is due to the fact that the payment of taxes and mandatory payments worsen the financial situation of taxpayers – individuals, and the fight against poverty has been declared a priority task of the state and local authorities. The study found that individuals, including non-working pensioners, bear a significant financial burden, which is caused, among other things, by the inability to shift the responsibility for paying taxes to someone, and therefore the number of people whose incomes are less than the subsistence level does not decrease, differentiation of the population does not decrease in terms of income. Recommendations on compensatory instruments to increase the income of the population are made.